2011
DOI: 10.1111/j.1468-0475.2010.00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Aversion and Sorting into Public Sector Employment

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
83
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 18 publications
7
83
0
1
Order By: Relevance
“…Based on this finding, they conclude that the positive relationship found in standard models is not structural but rather reflects unobserved heterogeneity. (Bellante et al 1981, Christofides et al 2002, Hartog et al 2002, Pfeifer 2011. 2 In addition, the public sector has long experienced serious difficulty recruiting high-quality labour.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this finding, they conclude that the positive relationship found in standard models is not structural but rather reflects unobserved heterogeneity. (Bellante et al 1981, Christofides et al 2002, Hartog et al 2002, Pfeifer 2011. 2 In addition, the public sector has long experienced serious difficulty recruiting high-quality labour.…”
Section: Introductionmentioning
confidence: 99%
“…and showed that the probability of choosing to work in the public sector increases as the degree of risk aversion increases. A recent study using the large scale German Socio Economic Panel found that risk averse workers tend to sort into public sector employment while risk taking is rewarded with higher wages in the private sector (Pfeifer, 2011). With the use of revealed risk preferences data, Buurman et al (2012) validate the argument that public workers are significantly less likely to choose the risky option (lotteries).…”
Section: Literaturementioning
confidence: 59%
“…It means that if the wage is similar there could be a queue to enter in the public sector. Bonin et al (2007) and Pfeifer (2011), using German Socioeconomic Panel data, find that the probability of being employed in the public sector is higher for risk adverse workers.…”
Section: A Literature Surveymentioning
confidence: 99%
“…Finally there is a third group, composed of few studies, that tries to investigate the peculiar characteristics of public employees, including civil servants' motivations, such as altruism and mission oriented (see for example Francois, 2000;Besley andGhatak, 2005, Buurman et al, 2012), the different degree of aversion to risk of public and private employees (Bellante and Link, 1981;Bonin et al, 2007;Pfeifer, 2011), the great attractiveness for public employees of high job security (Cappellari, 2002) and low wage mobility (Budria, 2010;Postel-Vinay and Turon, 2007). For example, Bellante and Link (1981) suggest that if the sorting process in the public and private sector depends on the degree of risk aversion, then those individuals with a high degree of aversion to risk will be more likely than others to seek employment in the public sector.…”
Section: A Literature Surveymentioning
confidence: 99%